Investigation of factors influencing the precipitation of iron oxides from Fe(II) containing solutions - Gotić, Marijan; Musić, Svetozar; Popović, Stanko, fizičar; Sekovanić, Lavoslav (2008)
Summary: Factors that influence the precipitation of iron oxides from Fe(II) containing solutions were investigated by X-ray powder diffraction, 57Fe Mössbauer and FT-IR spectroscopies, FE SEM and EDS techniques. Near spherical aggregates of spindle-shape goethite particles were obtained by oxidation of 0.1 mol dm–3 FeSO4 solution (suspension) with pure oxygen at 90 °C. Wide and thin goethite particles elongated along the crystallographic c-axis were formed in parallel. With the addition of tetramethylammonium hydroxide to 0.1 mol dm–3 FeSO4 solution (suspension) substoichiometric magnetite (Fe3-xO4) particles were additionally formed. They were dominant at pH > 12.5. Mössbauer spectroscopy was used to calculate the stoichiometries of Fe3-xO4 particles. Very small magnetite particles (20–100 nm) showed a tendency to aggregate. The twinning effect of octahedral magnetite particles (> 200 nm) was observed. A drastic effect on the properties of iron oxide precipitates was achieved by adding H3PO4 to the precipitation system containing 0.1 mol dm–3 FeSO4 + 0.01 mol dm–3 H2SO4 solution at the start. In dependence on the concentration of the added H3PO4, nanosize goethite particles about 15–25 nm in size, or poor crystalline ferrihydrite particles (two-line ferrihydrite) were obtained. The EDS analyses of the precipitates did not show any significant change in the sulphur content, whereas the phosphorous content gradually increased in the precipitates with an increase in the added H3PO4. In high concentrations phosphates completely suppressed the formation of goethite under given experimental conditions, and phosphated ferrihydrite was formed instead
Bibliografija: 21 jed.
Sažetak
Keywords: Željezni oksidi -- Magnetit -- Getit -- Nanočestice -- Ferihidrit -- Fosfati